PENGARUH STRUKTUR MODAL, PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Abraham Friederick; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2023)
The main purpose of this research is to analyze the effect of capital structure, profitability, leverage, and firm size towards firm value on listed manufacturing companies in Indonesia Stock Exchange (IDX) in the period of 2018-2020. The sample used in this research consists of 65 companies which are collected by using purposive sampling method and analized by using eviews 12 program. The result shown in this research indicates that capital structure and profitability has positive and significant effect on firm value, firm size has significant and negative effect on firm value, and leverage has not significant and negative effect on firm value.